2011
DOI: 10.1080/10550887.2011.609808
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Evidence-Based Pharmacological Treatments Among Community-Based Addiction Treatment Programs Targeting Vulnerable Patient Groups

Abstract: A national sample of addiction treatment Program Directors (N = 296) were assessed regarding their attitudes about pharmacological treatment for addiction disorders. Multivariable analyses indicate that directors who worked in organizations affiliated with research institutions and who had more professional experience had significantly more positive attitudes about a range of pharmacological therapies. Also, directors in organizations serving higher percentage homeless clients and clients with severe and persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Secondly, we also deliberated whether studies of variation in the uptake of “evidence-based practices” should be regarded as knowledge mobilisation research. We took the view that, even if a study explicitly labelled particular practices as evidence-based, then a study which only investigated attitudes towards those treatments [ 27 ] or variations in uptake was not strictly knowledge mobilisation research. It would only be knowledge mobilisation research, we decided, if there was some investigation into the processes of uptake of the practice or if there was an explicit initiative to promote the implementation of the evidence-based practice (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, we also deliberated whether studies of variation in the uptake of “evidence-based practices” should be regarded as knowledge mobilisation research. We took the view that, even if a study explicitly labelled particular practices as evidence-based, then a study which only investigated attitudes towards those treatments [ 27 ] or variations in uptake was not strictly knowledge mobilisation research. It would only be knowledge mobilisation research, we decided, if there was some investigation into the processes of uptake of the practice or if there was an explicit initiative to promote the implementation of the evidence-based practice (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…5 However, there are several barriers that prevent homeless individuals from receiving this evidencebased treatment, including fragmented and stigmatizing medical care, especially around episodes of incarceration, and the unfounded belief that treatment is unsuccessful in people who lack stable housing. [6][7][8][9][10] To overcome these barriers, innovative methods, such as provision of medications for OUD within harm reduction agencies, mobile methadone vans, and buprenorphine prescribing by street medicine teams, have been deployed and demonstrate the ability to reach larger populations of homeless and unstably housed patients. 9,[11][12][13] Because brick-and-mortar clinics may be more sustainable, there has been increased interest in developing office-based addiction treatment (OBAT) programs specifically for people experiencing homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Some physicians report concern about deception, suspicion of patient reported withdrawal symptoms [ 27 ], or worry that such patients would be disproportionately late to appointments [ 22 ]. Negative provider attitudes can also affect buprenorphine treatment rates; Krull et al [ 28 ] found that directors of addiction treatment programs serving homeless patients generally had negative attitudes towards buprenorphine use, indicating a need for education of public service providers about the clinically efficacy of buprenorphine.…”
Section: Causes Of Treatment Disparitiesmentioning
confidence: 99%
“…No significant differences in retention rates were found due to age, ethnicity, employment, or housing status. In a separate study of homeless patients, buprenorphine treatment was also associated with obtaining housing [ 28 ].…”
Section: Benefits Of Integration Into Public Sectormentioning
confidence: 99%